S is for Southern : a guide to the South, from absinthe to zydeco - DiBenedetto, David (Harper Wave, an imprint of Harper Collins Publishers, 2017)
"From the bestselling authors of The Southerner's Handbook, Good Dog, and The Southerner's Cookbook comes a lively compendium of Southern tradition and contemporary culture. The American South is a multifaceted region with its own vocabulary, peculiarities, and cultural touchstones. Even for those born in the South, the unspoken rules--layered in local nuances and complexities--can sometimes be confounding. Tennessee whiskey may technically be bourbon, but don't let anyone in Kentucky hear you call it that. And bless your heart, don't you dare make the mistake of confusing a magnolia blossom with a Japanese tulip. Now, from the editors of Garden & Gun--the magazine known as "the soul of the South"--comes this encyclopedia of Southern living, culture, and history. Covering age-old traditions and current zeitgeists, S Is for Southern includes more than 500 entries spanning every letter of the alphabet, from absinthe to zydeco. The book also includes 100 signature essays from notable Southern writers, including: John Meacham on the Civil War, Sean Brock on Waffle House, Roy Blount Jr. on humidity, Jessica Harris on field peas, Jason Isabel on The Atlanta Braves, Jack Hitt on Pluff Mud, The Lee Brothers on boiled peanuts, Jonathan Miles on Larry Brow, Julia Reed on the Delta. Informative and irreverent, illustrated with black-and-white line drawings throughout, S Is for Southern celebrates and demystifies the traditions of the South, and is a must-read for all fans of the region and culture enthusiasts"--Resumé vydavatele